Electro-thermal mapping of polymer electrolyte membrane fuel cells with a fractal flow-field. (15th December 2021) - Bethapudi, V.S.; Hack, J.; Hinds, G.; Shearing, P.R.; Brett, D.J.L.; Coppens, M.-O.
Graphical abstract: Highlights: First electro-thermal mapping of lung-inspired fractal flow-field PEMFC. Better electrochemical performance of lung-inspired PEMFC over conventional PEMFC. Homogeneous current distribution and higher surface temperatures in fractal PEMFC. Uniform and sustained operation of fractal flow field with better water management. Abstract: Electro-thermal maps of a polymer electrolyte membrane fuel cell (PEMFC) show the spatial distribution of current density and temperature, which is useful to evaluate their performance. Here, electro-thermal mapping is carried out for the first time on a PEMFC with a fractal cathode flow-field, the design of which emulates the efficient, scalable air transport inside the lungs. Such maps are compared with those of a conventional single-serpentine flow-field PEMFC. Each cell's performance is characterised by analysing the surface distribution of current density and temperature at different reactant relative humidity (RH) and cell voltage. Relationships are shown between segment current densities and surface temperatures, and between reactant relative humidity and cell operating conditions. The cells with a fractal flow-field deliver better electrochemical performance and exhibit more homogeneous current distributions compared to those with a single-serpentine flow-field, in which the current distribution is non-uniform due to cell flooding. The surface temperatures are higher in cells with a fractal flow-field than in those with a single-serpentine flow-field, consistent with the observed cell performances. In addition, electrochemical impedance spectroscopy characterisation indicates flooding in the single-serpentine cells, but not in the fractal cells.